2016
DOI: 10.18632/oncotarget.7497
|View full text |Cite
|
Sign up to set email alerts
|

Targeting FXYD2 by cardiac glycosides potently blocks tumor growth in ovarian clear cell carcinoma

Abstract: Ovarian clear cell carcinoma (OCCC) is an aggressive neoplasm with a high recurrence rate that frequently develops resistance to platinum-based chemotherapy. There are few prognostic biomarkers or targeted therapies exist for patients with OCCC. Here, we identified that FXYD2, the modulating subunit of Na+/K+-ATPases, was highly and specifically expressed in clinical OCCC tissues. The expression levels of FXYD2 were significantly higher in advanced-stage of OCCC and positively correlated with patients' prognos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 40 publications
(43 reference statements)
2
21
0
Order By: Relevance
“…As anticancer agents, cardiac glycosides triggered different cell death mechanisms including the intrinsic or the extrinsic pathway of apoptosis (Schneider et al, 2018, Juncker et al, 2011). Furthermore, cardiac glycosides induced autophagic cell death was described in breast, ovarian, colorectal, and lung cancer cells (Farah et al, 2016, Hsu et al, 2016, Kang et al, 2016, Wang et al, 2012). More recently, the ability of cardiac glycosides to trigger immunogenic cell death were reported (Diederich et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As anticancer agents, cardiac glycosides triggered different cell death mechanisms including the intrinsic or the extrinsic pathway of apoptosis (Schneider et al, 2018, Juncker et al, 2011). Furthermore, cardiac glycosides induced autophagic cell death was described in breast, ovarian, colorectal, and lung cancer cells (Farah et al, 2016, Hsu et al, 2016, Kang et al, 2016, Wang et al, 2012). More recently, the ability of cardiac glycosides to trigger immunogenic cell death were reported (Diederich et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Deficiency of FXYD2 led to tumor growth suppression, which indicated that FXYD2 had the possibility to be antitumor target. [ 32 ]…”
Section: Discussionmentioning
confidence: 99%
“…As anticancer agents, CGs triggered different cell death mechanisms including the intrinsic or the extrinsic apoptosis (Juncker et al, 2011 ; Cerella et al, 2015 ). Furthermore, CG-induced autophagic cell death was described in breast (Farah et al, 2016 ), ovarian (Hsu et al, 2016 ), colorectal (Kang et al, 2016 ), nerve system (Radogna et al, 2016 ), or lung cancer cells (Wang et al, 2012 ). More recently, the ability of CGs to trigger anoikis (Pongrakhananon et al, 2014 ) and immunogenic cell death (Menger et al, 2012 , 2013 ; Diederich et al, 2017 ) were reported.…”
Section: Introductionmentioning
confidence: 99%